2017
DOI: 10.4081/jae.2017.639
|View full text |Cite
|
Sign up to set email alerts
|

Spectra evolution over on-vine holding of Italia table grapes: prediction of maturity and discrimination for harvest times using a Vis-NIR hyperspectral device

Abstract: Measurement of certain grape quality parameters (sugars, acidity, and pH-value) is essential for the determination of the optimum harvest time. Non-destructive analytical techniques, including near infrared (NIR) spectroscopy, can be valid alternatives to traditional analytical methods for the determination of maturity indexes, enabling the possibility of on-field applications. This work aims to study the reliability to monitor spectra changes related with ripening of table grapes and to select optimal wavelen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The obtained values of R 2 of prediction were 0.92 for both PLS regression and Neural Networks with RMSEP of 0.94 • Brix and 0.96 • Brix, respectively. Hence, a good capacity of correlation was achieved in numerous other works on prediction of TSS for table and wine grapes [24,38,57,58].…”
Section: Discussionmentioning
confidence: 89%
“…The obtained values of R 2 of prediction were 0.92 for both PLS regression and Neural Networks with RMSEP of 0.94 • Brix and 0.96 • Brix, respectively. Hence, a good capacity of correlation was achieved in numerous other works on prediction of TSS for table and wine grapes [24,38,57,58].…”
Section: Discussionmentioning
confidence: 89%
“…In these works, two different spectral ranges (400-1000 nm and 900-1700 nm) were used to determine the grape quality parameters such as Phenolic compounds, TSS, pH, Titratable Acidity and Antioxidant activity. The best prediction results gathered with the PLS regression achieved R 2 of 0.86 and standard error of prediction (SEP) values of 2.62 and 3.05 mg/g for Nonacylated and Total Anthocyanins [2,39]; R 2 of 0.88, 0.89 and 0.84 and RMSEP values of 0.95 • Brix, 35.6 mg/L and 0.13 g/L CE for TSS, Anthocyanins and Tannins, respectively [3,40,42]. Additionally, in these works, values of R 2 of 0.81, 0.78 and 0.62 and RMSEP of 0.25, 0.04 g/100g tartaric acid and 48.98 mg/100g Trolox for pH, Titratable Acidity and Antioxidant Activity, respectively were reported [40,42].…”
Section: Regression Models For Grape Composition Predictionmentioning
confidence: 98%
“…The best prediction results gathered with the PLS regression achieved R 2 of 0.86 and standard error of prediction (SEP) values of 2.62 and 3.05 mg/g for Nonacylated and Total Anthocyanins [2,39]; R 2 of 0.88, 0.89 and 0.84 and RMSEP values of 0.95 • Brix, 35.6 mg/L and 0.13 g/L CE for TSS, Anthocyanins and Tannins, respectively [3,40,42]. Additionally, in these works, values of R 2 of 0.81, 0.78 and 0.62 and RMSEP of 0.25, 0.04 g/100g tartaric acid and 48.98 mg/100g Trolox for pH, Titratable Acidity and Antioxidant Activity, respectively were reported [40,42]. These outcomes are very close to the results presented in this study.…”
Section: Regression Models For Grape Composition Predictionmentioning
confidence: 98%
See 1 more Smart Citation
“…Authors obtained 100% correct classification of samples belonging from five harvest times [8]. Moreover, in a recent study, [42] showed that analyzing spectra changes over time during on-vine holding of table grapes was possible to monitor ripening and to correctly classify grapes by harvest time, using only 14 wavelengths. These findings encourage further implementation of this method to monitor ripening of table grapes in the vineyard and better define the most suitable harvest time.…”
Section: Classification Based On Production Systemmentioning
confidence: 99%